Measured Analysis of Noise Reduction Effect for Urban Rapid Rail Transit Viaducts - LU Sheng’an; LIN Haifeng (Chengshi guidao jiaotong yanjiu)
［Objective］ To reduce the impact of elevated lines in urban rapid rail transit on environmental noise, multiple noise-reduction measures such as near-track sound barriers and ballast bed sound-absorbing panels are adopted. On-site measurements and analyses should combine with on-site operating conditions to verify the effectiveness of trackside noise reduction measures in reducing environmental noise. ［Method］ In the case study of the already operating Line S1 of Wenzhou Urban Rapid Rail Transit, the environmental noise in the viaduct section of this line is measured on site. The noise reduction effects of near-track sound barriers and ballast bed sound-absorbing panels for the environmental noise under different train running speeds are compared and analyzed, and the influence characteristics of different noise reduction measures on the viaduct section noise are explored. ［Result & Conclusion］ The near-track sound barrier reduces the maximum instantaneous A-weighted time-domain sound pressure level (hereinafter abbreviated as “A-weighted level”) on the viaduct inner and outer sides by approximately 20 to 21 dB(A). At the position 7.5 meters away from the track center line and 7.5 meters above the rail surface, the A-weighted level in the 500 Hz and 800-1 000 Hz frequency bands are respectively reduced by 6 to 11 dB(A) and 17 to 21 dB(A). The ballast bed sound-absorbing panels can further reduce the trackside noise on and outside the viaduct. Compared with the working conditions where only the near-track sound barriers are installed, when using the sound-absorbing panels, the maximum instantaneous A-weighted level on the viaduct is further reduced by 14 to 17 dB(A) with the same train running speed, and the A-weighted level is reduced by 7 to 8 dB(A) and 5 to 7 dB(A) respectively for the noise in the 500 Hz and 800 - 1 000 Hz frequency bands at the same measuring point outside the viaduct.